Evaluation of a steam pasteurization process in a commercial beef processing facility - Nutsch, Abbey L.; Phebus, Randall K.; Riemann, M. James; Schafer, David E.; Boyer, John E.; Wilson, R. Craig; Leising, Jerome D.; Kastner, Curtis L. (My University, 2008)
The effectiveness of a steam pasteurization process for reducing naturally occurring bacterial populations on freshly slaughtered beef sides was evaluated in a large commercial facility. Over a period of 10 days, 140 randomly chosen beef sides were microbiologically analyzed. Each side was sampled immediately before, immediately after, and 24 h after steam pasteurization treatment. Total aerobic bacteria (APC), Escherichia coli (generic), coliform, and Enterobacteriaceae populations were enumerated. The process significantly (P ≤ 0.01) reduced mean APCs from 2.19 log CFU/cm2 before treatment to 0.84 log CFU/cm2 immediately after and 0.94 log CFU/cm2 24 h after treatment. Before pasteurization (8 s steam exposure), 16.4% of carcasses were positive for generic E. coli (level of 0.60 to 1.53 log CFU/cm2), 37.9% were positive for coliforms (level of 0.60 to 2.26 log CFU/cm2), and 46.4% were positive for Enterobacteriaceae (level of 0.60 to 2.25 log CFU/cm2). After pasteurization, 0% of carcasses were positive for E. coli, 1.4% were positive for coliforms (level of 0.60 to 1.53 log CFU/cm2), and 2.9% were positive for Enterobacteriaceae (level of 0.60 to 1.99 log CFU/cm2). Of the 140 carcasses evaluated, one carcass was positive for Salmonella spp. before treatment (0.7% incidence rate); all carcasses were negative after steam treatment. This study indicates that steam pasteurization is very effective in a commercial setting for reducing overall bacterial populations on freshly slaughtered beef carcasses. The system may effectively serve as an important critical control point for HACCP systems at the slaughter phase of beef processing. In conjunction with other antimicrobial interventions (mandated by USDA to achieve zero tolerance standards for visible contamination) and good manufacturing practices, this process can play an important role in reducing the risk of pathogenic bacteria in raw meat and meat products.
Keywords: Beef; Steam; Pasteurization; Decontamination; E. coli